Corticospinal tract structure and excitability in patients with anterior cruciate ligament reconstruction: A DTI and TMS study - Lepley, Adam S. (Neuroimage Clin, 2019)
BACKGROUND: Underlying neural factors contribute to poor outcomes following anterior cruciate ligament reconstruction (ACLR). Neurophysiological adaptations have been identified in corticospinal tract excitability, however limited evidence exists on neurostructural changes that may influence motor recovery in ACLR patients. OBJECTIVE: To 1) quantify hemispheric differences in structural properties of the corticospinal tract in patients with a history of ACLR, and 2) assess the relationship between excitability and corticospinal tract structure. METHODS: Ten participants with ACLR (age: 22.6 ± 1.9 yrs; height: 166.3 ± 7.5 cm; mass: 65.4 ± 12.6 kg, months from surgery: 70.0 ± 23.6) volunteered for this cross-sectional study. Corticospinal tract structure (volume; fractional anisotropy [FA]; axial diffusivity [AD]; radial diffusivity [RD]; mean diffusivity [MD]) was assessed using diffusion tensor imaging, and excitability was assessed using transcranial magnetic stimulation (motor evoked potentials normalized to maximal muscle response [MEP]) for each hemisphere. Hemispheric differences were evaluated using paired samples t-tests. Correlational analyses were conducted on structural and excitability outcomes. RESULTS: The hemisphere of the ACLR injured limb (i.e. hemisphere contralateral to the ACLR injured limb) demonstrated lower volume, lower FA, higher MD, and smaller MEPs compared to the hemisphere of the non-injured limb, indicating disrupted white matter structure and a reduction in excitability of the corticospinal tract. Greater corticospinal tract excitability was associated with larger corticospinal tract volume. CONCLUSIONS: ACLR patients demonstrated asymmetry in structural properties of the corticospinal tract that may influence the recovery of motor function following surgical reconstruction. More research is warranted to establish the influence of neurostructural measures on patient outcomes and response to treatment in ACLR populations.